2018
DOI: 10.1159/000488384
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative Neoplasms in Danish Twins

Abstract: Objective: Myeloproliferative neoplasms (MPNs) are a heterogeneous group of diseases characterized by clonal hyperproliferation of immature and mature cells of the myeloid lineage. Genetic differences have been proposed to play a role in the development of MPNs. Monozygotic twin pairs with MPNs have been reported in a few case reports, but the MPN concordance pattern in twins remains unknown. Method: All twin pairs born in the period 1900–2010 were identified in the nationwide Danish Twin Registry. Only pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Twin studies from the Scandinavia have shown an increased familial risk of cancer, and in chronic myeloid neoplasms, Andersen et al 16 demonstrated a casewise concordance (cc) rate of 15% among monozygotic (MZ) twins compared to 0% among dizygotic (DZ) twins p = 0.016, suggesting a genetic predisposition. In addition, it has been known for decades that some germline aberrancies predispose to hematological cancer such as AML and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies from the Scandinavia have shown an increased familial risk of cancer, and in chronic myeloid neoplasms, Andersen et al 16 demonstrated a casewise concordance (cc) rate of 15% among monozygotic (MZ) twins compared to 0% among dizygotic (DZ) twins p = 0.016, suggesting a genetic predisposition. In addition, it has been known for decades that some germline aberrancies predispose to hematological cancer such as AML and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…A Danish cohort study previously reported concordance for MPN in 15% of monozygotic twins; 29 although the authors concluded that this might reflect genetic predisposition to MPN, it may be that these cases were due to an in utero origin and transplacental transmission, as concordant cases were not observed in dizygotic twins. Furthermore, concordance of clonal hematopoiesis with identical somatic mutations in elderly twins has also been reported, suggesting that clones that arise in utero might even persist lifelong until old age without causing disease 30 , 31 .…”
Section: Discussionmentioning
confidence: 95%
“…The role of genetic predisposition and landscape in the development of MPN have been quite extensively elucidated [13]. The discovery of driver genes JAK2, CALR, and MPL is an important milestone in unrevealing the myths of MPN, hence the World Health Organization has included mutations in all three genes as the hallmark of MPN [1].…”
Section: Hypercellularity With Clusteredmentioning
confidence: 99%